I2(u)-convergence of double sequences of order (?, ?) - Altin, Yavuz; Colak, Rifat; Torgut, Birgul (Walter de Gruyter Gmbh, 2015)
In this paper, we introduce and examine the concepts of I-2(u)-convergence of order (alpha, beta) and uniformly strong p-Cesaro summability of order (alpha, beta), of double sequences of complex (or real) numbers, where alpha, beta are real numbers such that 0 < alpha, beta <= 1. Also, we establish the main results and prove some inclusion relations between uniformly strong p-Cesaro summability and I-2(u)-convergence of order (alpha, beta).
Keywords: Statistical convergence; Cesaro summability; density; double sequence